Stranded marine debris on the touristic beaches in the south of Bali Island, Indonesia: The spatiotemporal abundance and characteristic. (December 2021) - Suteja, Yulianto; Atmadipoera, Agus Saleh; Riani, Etty; Nurjaya, I Wayan; Nugroho, Dwiyoga; Purwiyanto, Anna Ida Sunaryo
Abstract: Stranded marine debris (MD) has become a hot topic on Bali Island because it threatens coastal tourism sustainability. This study aims to investigate the spatiotemporal abundance and characteristics of MD on 14 touristic beaches in Bali Island. Sampling is carried out twice every season by adapting methods from NOAA's MD program. We found that the average MD abundance and weight were 0.356 ± 0.366 items/m 2 and 4.057 ± 3.892 g/m 2, respectively. Plastic dominated the MD based on abundance (86.9%) and weight (40.1%). Plastic bags, straws, and plastic cups are the most common items among plastics. The MD is originated from Indonesia and is dominated by land-based sources. The beaches are categorized as dirty in the rainy seasons and clean in the dry seasons. Statistically, the MD based on abundance, weight, category, source, and level of cleanliness varied significantly between seasons. Graphical abstract: Unlabelled Image Highlights: The average marine debris during the rainy season was higher (4 times based on abundance and 2 times based on weight) than the dry season. Spatially, routine cleaning activities, proximity to rivers, and land use affect the marine debris abundance. Temporally, the abundance of marine debris is influenced by rainfall and ocean circulation. Marine debris weight associated with the abundance and category.